2008
DOI: 10.18597/rcog.415
|View full text |Cite
|
Sign up to set email alerts
|

Las enfermedades intercurrentes durante la gestación y sus consecuencias sobre el peso del recién nacido

Abstract: Objetivo: verificar si las enfermedades intercurrentes presentes en la gestación aumentan las probabilidades de que la madre tenga un niño con bajo peso al nacer (BPN).Metodología: se trata de un estudio de casos y controles realizado en el periodo de abril a noviembre del 2003, en la ciudad de Río Grande/RS, Brasil. La recolección de datos se hizo a través de un cuestionario aplicado a 547 madres que presentaron parto en las maternidades de los dos hospitales de este municipio.Resultados: la presencia de hipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…However, to our surprise, only 25% of patients with pre‐eclampsia in our sample were in this age group. The threat of abortion was also a common finding in our study, being reported in 20% of cases (studies conducted in the state of Rio Grande do Sul point to a rate of about 4% [Stein‐Backes and Flores‐Soares, 2008]). In our review of the literature we did not find description of similar findings.…”
Section: Discussionsupporting
confidence: 66%
“…However, to our surprise, only 25% of patients with pre‐eclampsia in our sample were in this age group. The threat of abortion was also a common finding in our study, being reported in 20% of cases (studies conducted in the state of Rio Grande do Sul point to a rate of about 4% [Stein‐Backes and Flores‐Soares, 2008]). In our review of the literature we did not find description of similar findings.…”
Section: Discussionsupporting
confidence: 66%
“…A recomendação da Organização Mundial da Saúde (OMS) é que a taxa de cesárea seja no máximo 15% (6) . Os casos de gestantes com hipertensão, por exemplo, estão acarretando um aumento na incidência de cesáreas, pois são distúrbios considerados graves durante a gestação (7) .…”
Section: Introductionunclassified